The Prevalence of Requirements of the application of Crisis Management Practices in Yemeni Banks - Al-Mutari, Ahmed Ali Hussein; Rafik, Mohammed Yahya; Al Ashool, Mohammed Abdullah Ahmed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aims at identifying the Prevalence of requirements for applying crisis management practices and the factors that limit the application of these practices in Yemeni banks. The descriptive and analytical approach was used and a questionnaire was designed to collect the primary data. The study used a class-specific sample of 82 units. After analyzing the data using the SPSS، The study found that the average of Prevalence of requirements for applying crisis management practices in Yemeni banks reached 3.85، a relatively high level، indicating that the sample of the study considers that the requirements of applying crisis management practices in Yemeni banks are available. The study also found that there are many obstacles that limit the application of crisis management practices in Yemeni banks.